Is Immune Therapy Plus Chemotherapy More Effective Than Immune Therapy Alone for Unresectable Recurrent Nasopharyngeal Carcinoma? - Zhou, Xin; Niu, XiaoShuang; Liu, PeiYao; Ou, Dan; Zhu, Yi; Wang, XiaoShen (Frontiers in Immunology, 2021)
Objective: To evaluate whether the combination of immune checkpoint inhibitor (ICI) with chemotherapy is more effective than ICI alone in the treatment of recurrent, locoregionally advanced, unresectable nasopharyngeal carcinoma (RAU-NPC), which has progressed after second line chemotherapy. Methods and materials: Patients with RAU-NPC that progressed after second chemotherapy were prescribed ICI once every 3 weeks, either alone or combined with chemotherapy at the discretion of treating physicians, until confirmed disease progression, unacceptable toxicity, or voluntary withdrawal. The primary endpoint was the objective response rate (ORR). The secondary endpoints included safety, duration of response (DOR), and progression-free survival (PFS). Results: From June 2016 to July 2021, 28 patients were enrolled in this study.21 patients received ICI plus chemotherapy, and 7 patients received ICI alone. Altogether, there were 7 (25%) complete response (CR) and 12 (42.8%) partial response (PR), respectively. Stable disease (SD) and progressive disease (PD) were defined in 4 (14.3%) and 5 (17.8%) cases, respectively. The ORR was 19 out of 28 (67.8%). The disease control rate (DCR) was 23 out of 28 (82.1%).Two patients (28.6%) in the ICI alone group and five (23.8%) in the combination group achieved CR (P=0.801). 2 patient (28.6%) in the ICI alone group and 10 (47.6%) in the combination group achieved PR (P=0.378). With a median follow-up of 16 months (2-61 months), five patients terminated ICI due to disease progression, one patient was lost to follow-up, and the remaining 22 patients continued with ICI. Neither the median PFS nor the median DOR was reached. All observed adverse events were defined as ≤ Grade 2. Conclusion: ICI alone or combined with chemotherapy demonstrated promising antitumor activity in RAU-NPC patients that progressed after second line chemotherapy, with a low toxicity profile. Compared with ICI alone, chemotherapy plus ICI did not improve CR or PR in our study.